2005
DOI: 10.1038/sj.cr.7290271
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factors 4 and 5: the yin and yang regulators of cellular proliferation

Abstract: Krüppel-like factors (KLFs) are evolutionarily conserved zinc finger-containing transcription factors with diverse regulatory functions in cell growth, proliferation, differentiation, and embryogenesis. KLF4 and KLF5 are two closely related members of the KLF family that have a similar tissue distribution in embryos and adults. However, the two KLFs often exhibit opposite effects on regulation of gene transcription, despite binding to similar, if not identical, cis-acting DNA sequences. In addition, KLF4 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
239
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(249 citation statements)
references
References 39 publications
7
239
2
1
Order By: Relevance
“…The intestinal epithelium is a highly polarized system containing terminally differentiated epithelial cells at villi and proliferating and progenitor cells in crypts (14). As the KLF5 protein is highly abundant in the crypt cell population with a diminishing gradient as cells migrate toward the villus (27,30,31), SMURF2 may form an opposite gradient along the crypt/ villus axis or contribute to establishing the polarity of the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal epithelium is a highly polarized system containing terminally differentiated epithelial cells at villi and proliferating and progenitor cells in crypts (14). As the KLF5 protein is highly abundant in the crypt cell population with a diminishing gradient as cells migrate toward the villus (27,30,31), SMURF2 may form an opposite gradient along the crypt/ villus axis or contribute to establishing the polarity of the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Although at least some of the functions of KLF4 and KLF6 seem to be similar, KLF5 has been proposed to have complementary functions to those of KLF4 (REF. 14), in that they have opposing effects on the expression of their shared target genes [64][65][66] . It is not entirely clear whether the settings in which KLF4 functions as an oncogene are similar to those in which KLF5 functions as a tumour suppressor, or vice versa.…”
Section: Klf4 As An Oncogenementioning
confidence: 99%
“…For example, KLF6 has been described as a tumour suppressor in multiple cancer types, including prostate carcinomas 13 . Remarkably, KLF4 and KLF5 have been described as both tumour suppressors and oncogenes 14 .…”
mentioning
confidence: 99%
“…In general, KLF4 is usually present in well-differentiated, non-proliferating cells, where it serves the role of growth suppressor and is activated strongly in fibroblasts arrested by serum withdrawal (reviewed in Ghaleb et al, 2005). Profiling experiments have shown that KLF4 activates genes that inhibit proliferation, and represses genes that promote it Whitney et al, 2006;Swamynathan et al, 2008).…”
mentioning
confidence: 99%